Cancer Profile in South Jakarta : A 5-year descriptive study - Gondhowiardjo, Soehartati Argadikoesoema; Raharjo, Febryono Basuki; Hudiya, Elian; Priharto, R Koesmedi; Yekti, Widyastuti Endro (Perhimpunan Dokter Spesialis Onkologi Radiasi Indonesia (PORI), 2018)
There has been an effort of cancer registry in Cancer Control Program, especially Hospital-based, but it would not be useful if the data and procedure was not standardized. This study was a cross-sectional study with cancer data collected from every health facility in South Jakarta from 2017, April to May. Inclusion criteria was every patient that resided in South Jakarta from 2008, January 1st to 2012, December 31st with no exclusion criteria. Five most common cancers for male are hematopoietic and reticuloendothelial systems, nasopharynx, lung, lymph nodes, and liver cancer, respectively. Five most common cancers in female are breast, cervix uteri, ovarium, hematopoietic and reticuloendothelial systems, thyroid gland cancer, respectively. Cancer patients were comprised by female a lot more than male with 1.86:1 frequency comparison. Compared to data from Malaysia and Singapore in the same period of time, there were some differences in cancer profile between the countries. Based on the data reviewed, the quality was not perfect, one of the examples is shortcoming of SriKandi form which was used to input the data, especially occupation data. This can be a refinement point for future research and registry of cancer in Indonesia